Metagenomic analysis reveals a marked divergence in the structure of belowground microbial communities at elevated CO 2 - Zhili He; Meiying Xu; Ye Deng; Sanghoon Kang; Laurie Kellogg; Liyou Wu; Joy D. Van Nostrand; Sarah E. Hobbie; Peter B. Reich; Jizhong Zhou (Ecology Letters, 2010)
Ecology Letters (2010) 13: 564–575 Abstract Understanding the responses of biological communities to elevated CO 2 (eCO 2 ) is a central issue in ecology, but little is known about the influence of eCO 2 on the structure and functioning (and consequent feedbacks to plant productivity) of the belowground microbial community. Here, using metagenomic technologies, we showed that 10 years of field exposure of a grassland ecosystem to eCO 2 dramatically altered the structure and functional potential of soil microbial communities. Total microbial and bacterial biomass were significantly increased at eCO 2 , but fungal biomass was unaffected. The structure of microbial communities was markedly different between ambient CO 2 (aCO 2 ) and eCO 2 as indicated by detrended correspondence analysis (DCA) of gene‐based pyrosequencing data and functional gene array data. While the abundance of genes involved in decomposing recalcitrant C remained unchanged, those involved in labile C degradation and C and N fixation were significantly increased under eCO 2. Changes in microbial structure were significantly correlated with soil C and N contents and plant productivity. This study provides insights into potential activity of microbial community and associated feedback responses of terrestrial ecosystems to eCO 2 .